Modeling the effects of environmental and ecological processes on the transport, mortality, growth and distribution of early stages of Cape Anchovy (Engraulis Encrasicolus) in the Benguela system - Parada, Carolina E (Department of Oceanography, 2014)
Bibliography: leaves 107-119.